Applying High-Value Care Principles in a Pediatric Case: A Workshop for Health Professions Students - Priya N. Jain; Steven Eagle; Miriam Schechter; Hai Jung H. Rhim; Rhonda Acholonu (Association of American Medical Colleges, 2020)
Introduction The cost of health care in the US is rapidly rising. Understanding the financial cost of medical care is an important competency for physicians and physicians-in-training. Medical students in their clinical clerkships are being exposed to health care decision-making often for the first time and are forming habits they will carry throughout their training and careers. Teaching high-value care (HVC) principles is crucial for students as they will be the future leaders in health care. Methods This 1-hour workshop was interactive and aimed to prepare medical students to apply HVC when making medical decisions. The topic of HVC was initially introduced by eliciting tests that students want to order and highlighting the concept of whether or not a test changes the management of the patient. This exercise was followed by a PowerPoint presentation which discussed HVC, Choosing Wisely guidelines in pediatrics, and how to communicate with parents and patients about this topic. Results Of third-year medical students, 125 participated in the workshop, with a survey response rate of 90% (n = 112). Ninety-nine percent reported that this workshop was helpful, and 97% reported that they will change their practice to reflect more cost-conscious care. Most students reported that their knowledge of HVC improved after the session, with 88% reporting scores of 3 (moderately improved) or 4 (significantly improved). Discussion This ready-to-implement workshop offered students an understanding of how the cost of medical care impacts patients and families and how to practice cost-conscious care in pediatrics.